IPTEKS SISTEM AKUNTANSI MANAJEMEN DALAM PENINGKATAN KINERJA MANAJERIAL DAN KARYAWAN BANK BRI DI MANADO - Pongilatan, Mariska; Ilat, Ventje (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
Management accounting system is a basic accounting information that is very important for managers and employees in making or determining decisions as well as identification in the organization. This study aims to analyze the management accounting systems improving the performance of managers and employees, and analyze whether their answers, and improve interpersonal skills. This research was conducted at BRI Bank in Manado. The study was conducted by analyzing the performance of managers and employees, and adjusting the number of employees with workload on each employee. this study describe that the management accounting system has an important influence in company can also help managers in making and determining decisions, controlling work activities that exist within the company so as to increase the performance of manager.Keywords:manajer,employee,performace,active,creative,innovative,description,interpersonal